A combinatorial approach increases SMN level in SMA model mice. Issue 17 (14th April 2022) - Dumas, Samantha A; Villalón, Eric; Bergman, Elizabeth M; Wilson, Kenneth J; Marugan, Juan J; Lorson, Christian L; Burnett, Barrington G
Abstract: Spinal muscular atrophy (SMA) is a neurodegenerative disease caused by reduced expression of the survival motor neuron (SMN) protein. Current disease-modifying therapies increase SMN levels and dramatically improve survival and motor function of SMA patients. Nevertheless, current treatments are not cures and autopsy data suggest that SMN induction is variable. Our group and others have shown that combinatorial approaches that target different modalities can improve outcomes in rodent models of SMA. Here we explore if slowing SMN protein degradation and correcting SMN splicing defects could synergistically increase SMN production and improve the SMA phenotype in model mice. We show that co-administering ML372, which inhibits SMN ubiquitination, with an SMN-modifying antisense oligonucleotide (ASO) increases SMN production in SMA cells and model mice. In addition, we observed improved spinal cord, neuromuscular junction and muscle pathology when ML372 and the ASO were administered in combination. Importantly, the combinatorial approach resulted in increased motor function and extended survival of SMA mice. Our results demonstrate that a combination of treatment modalities synergistically increases SMN levels and improves pathophysiology of SMA model mice over individual treatment.